ANALISIS PENGARUH PERPUTARAN KAS, PERPUTARANPIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS - Intan Sayida; Endang Lestari; Kezia Demelia; Galih Pratama (PROSIDING SERINA, 2021)
This study is aimed at looking at the effect of cash turnover, receivables turnover, and inventory turnover on profitability. The research method used in this study is a qualitative method where this study produces descriptive data in the form of written words. Sources of data using sources of document and journal references that can support research. Based on research, cash turnover has no effect on profitability. This shows that cash has not contributed effectively to profit. There is a market risk that can effect the company’s result of operations and cash flow, namely the risk of foreign exchange rates. Account receivable turnover has an effect on profitability. There is a risk in account receivable that credits and uncollected receivables can be ignored. So the value of receivable greatly affect’s the company’s receivable turnover ratio. Invenntory turnover does not affect profitability conditions of inventory turnover tend to be more stable, inventory does not experiences a drastic decline in value. The companies also carry out insurance on inventories of finished good and spare partsto prevent the risk of loss, fire and other risk